The Authenticity of Kemenkumham Decree Regarding Limited Liability Company with Husband and Wife Joint Assets Share Establishment Approval Based On Presumptio Iustae Causa Principles - Kayla Raissafitri; Naufal Afrian Noormansyah; Taupiqqurrahman (Jurnal Hukum dan Kenotariatan, 2023)
This research will be analyzing the authenticity of Kemenkumham Decree Regarding Limited Liability Company with Husband and Wife Joint Asset Shares Establishment Approval based on Presumptio Iustae Causa principles and the legal effect towards the Kemenkumham Decree if the Establishment Deed a quo declared annulled by the district court. This research is examined through several method, specifically using normative juridical research and statutory approach, also will be written in descriptive literature. The result of the research shows Kemenkumham Decree is considered as a state administration decree. Therefore, based on Presumptio Iustae Causa principle, the Kemenkumham Decree Regarding Limited Liability Company with Husband and Wife Joint Assets Share Establishment Approval that has been issued is an authentic decree. This principle implies that the Kemenkumham decree stands its authenticity for the sake of legal certainty, until an authorized decision from state administrative court proves otherwise and revokes its authenticity. The cancellation event of Limited Liability Company with Husband and Wife Joint Assets Share Establishment Deed condone by the District Court will not affect the authenticity of the Kemenkumham Decree. The authorized court that can revoke Kemenkumham Decree belongs to the State Administrative Court. Keywords: Kemenkumham Decree Authenticity; Limited Liability Company; Husband and Wife; Joint Asset Shares